Five Roots Pattern of Median Nerve Formation - Konstantinos Natsis; George Paraskevas; Maria Tzika (Acta Medica, 2016)
An unusual combination of median nerve’s variations has been encountered in a male cadaver during routine educational dissection. In particular, the median nerve was formed by five roots; three roots originated from the lateral cord of the brachial plexus joined individually the median nerve’s medial root. The latter (fourth) root was united with the lateral (fifth) root of the median nerve forming the median nerve distally in the upper arm and not the axilla as usually. In addition, the median nerve was situated medial to the brachial artery. We review comprehensively the relevant variants, their embryologic development and their potential clinical applications.